UPAYA PENCEGAHAN PENULARAN COVID-19 PADA MASYARAKAT SELAMA PSBB DI PROVINSI SUMATERA BARAT - Yeffi Masnarivan; Arinil Haq; Anggela Pradiva Putri (LLDIKTI Wilayah X, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Therefore, this study aimed to determine efforts to prevent the transmission of Covid-19 to the community during the PSBB in West Sumatra Province in This research is a quantitative study using a survey method. The study was conducted from April 30 to May 5, 2020 with a questionnaire using Googleform. The results showed that respondents are always used to avoid touching objects / surfaces in public areas. Many respondents are always used to physical distancing at least one meter from other people when outside the home. For worship during the PSBB, more than half of the respondents are always accustomed to avoiding worshiping at mosques / churches / monasteries / others. Most respondents or family members never smoke in and around the house. If there are migrants from an infected area around the respondent's domicile, they have followed quarantine for 14 days, either self-quarantine or a quarantine place that has been prepared and if there are any signs of Covid-19 around the respondent's domicile, they will immediately be taken to the nearest hospital according to the Covid-19 health protocol